Easy Microsoft Office Word 2003 - Steele, Heidi (Easy Ser., 2004)
Easy Microsoft Office Word 2003 takes the work out of learning Word 2003 by using short, easy-to-follow lessons that show you how to accomplish basic tasks quickly and efficiently! It is the perfect book for beginners who want to learn Microsoft¿s word processing application through a visual, full-color approach. More than 100 hands-on lessons are designed to teach the easiest, fastest, or most direct way to accomplish common Word tasks. The book is suited for new Word users, as well as those upgrading from an earlier version.